Vestibular evoked myogenic potential may predict the hearing recovery in patients with unilateral idiopathic sudden sensorineural hearing loss - Liang, Min; Wu, Hui; Chen, Jianyong; Zhang, Qin; Li, Shuna; Zheng, Guiliang; He, Jingchun; Chen, Xiangping; Duan, Maoli; Yang, Jun; Jin, Yulian (Frontiers in Neurology, 2022)
Objective This study investigates the association between vestibular function and prognosis in patients with unilateral idiopathic sudden sensorineural hearing loss (UISSNHL). Design A retrospective analysis of 64 patients with UISSNHL was performed. Pure tone audiometry and vestibular function tests for otoliths and semicircular canals were performed to assess the influence of vestibular functional status on the outcome of patients with UISSNHL. Results Patients with abnormal cervical vestibular evoked myogenic potential (cVEMP) or ocular vestibular evoked myogenic potential (oVEMP) responded less favorably to treatment. In the ineffective group, cVEMP was normal in four patients (6.3%) and oVEMPs in three (4.7%). Meanwhile, cVEMP was abnormal in 32 patients (50.0%) and oVEMP in 33 (51.6%). Better hearing recovery occurred in those with normal cVEMP (33.76 ± 15.07 dB HL improvement) or oVEMP (32.55 ± 19.56 dB HL improvement), but this was not the case in those with normal caloric tests. Patients with abnormalities in both cVEMP and oVEMP were less responsive to treatment and had worse hearing recovery than those with normal results in only one of the two tests. Conclusion Abnormal oVEMP and/or cVEMP results indicate poor auditory outcomes in patients with UISSNHL. Patients with impaired otolith organ function are likely to have a larger and more severe pathological change in their inner ear.